POST-CRISIS ECONOMIC SPECIALISATION PATTERNS OF ARGES COUNTY IN ROMANIA AND THE EU. MOVING TOWARDS SMART SPECIALIZATION - Ovidiu, PUIU; Cristina, SERBANICA (Strategii Manageriale)
Under the new European regional policy framework for 2014 – 2020, smart specialization is a key issue meant to highglight the unique characteristics and assets of each country/ region and to rally regional stakeholders and resources around an excellence-driven vision for their future. To this end, this paper provides a statistical analysis of specialization patterns in Arges county on the basis of GVA and employed population, using traditional absolute and relative measures. At the same time, the paper highlisgts the shifts in the local economy due to the economic crisis (2008 - 2010) and offers a number of possible further actions for smart specialisation.